Projeto e otimização de uma câmara de combustão de microturbinas para operação com biogás - Osvane Abreu Faria (2015)
Design of a small scale gas turbine reverse flow combustor is done by analytical methods and reviewed by numerical tools. With the objective of studying the applicability of the literature developed for conventional through flow large scale gas turbine combustor, a low cost and simple geometry burner is designed and used as start point for several numeric simulations and design reviews. The geometry is solved and analyzed regarding liner pressure loss, flame anchoring, outlet temperature gradient and combustion completion. Then the combustor is simulated with different biogas contents and again redesigned to achieve optimal performance with the renewable fuels. Although the initial analytically derived geometry served as a good starting point, the numeric simulation made large improvements possible. Accounting for phenomena and characteristics that only coupled Fluid-Thermochemical physics could describe, an extensive study of the flame-flow interdependence was done for the resultant combustor geometry, making combustion control possible by further refining flow patterns and distribution.